Explicație pas cu pas:
Formula pentru [tex]tg\frac{x}{2} [/tex] este:
[tex]tg\frac{x}{2}=\pm\sqrt{\frac{1-cosx}{1+cosx}}=\frac{sinx}{1+cosx}=\frac{1-cosx}{sinx}[/tex]
Totodata, si celelalte functii trigonometrice pot fi exprimate in functie de [tex]tg\frac{x}{2} [/tex]:
[tex]sinx=\frac{2tg\frac{x}{2}}{1+tg^2\frac{x}{2}}[/tex]
[tex]cosx=\frac{{1-tg^2\frac{x}{2}}}{{1+tg^2\frac{x}{2}}}[/tex]
[tex]tgx=\frac{2tg\frac{x}{2}}{1-tg^2\frac{x}{2}}[/tex]
[tex]tgx=\frac{1-tg^2\frac{x}{2}}{2tg\frac{x}{2}}[/tex]